Kluver-Bucy syndrome: A morbid consequences of post herpes simplex encephalitis - Ajay Halder; Uday Sankar Mandal; Subrata Halder; Abhinanda Biswas (Wolters Kluwer Medknow Publications, 2015)
Kluver-Bucy syndrome (KBS) is a neuropsychiatric behavioral disorder that is most commonly associated with damage to both of the anterior temporal lobes of the brain. Most commonly it is due to infection of herpes simplex encephalitis (HSE). Although computed tomography (CT), magnetic resonance imaging (MRI) and electroencephalography (EEG) suggest the injury to the temporal region of brain, the definitive diagnosis is only established by the finding of the viral antigen in brain. Previously viral antigen is obtained by biopsy, currently it is demonstrated by the polymerase chain reaction technique. As we all know, it is a very rare disorder and most of the literature relates to animal models rather than human cases. We here describe an important human case of KBS following HSE.